2018
DOI: 10.3390/children5070089
|View full text |Cite
|
Sign up to set email alerts
|

Fat Intake Reduction Strategies among Children and Adults to Eliminate Obesity and Non-Communicable Diseases in the Eastern Mediterranean Region

Abstract: Non-communicable diseases (NCDs) are the leading cause of mortality globally with an estimated 39.5 million deaths per year (72% of total death) in 2016, due to the four major NCDs: cardiovascular diseases, cancers, chronic respiratory diseases and diabetes. In the Eastern Mediterranean Region (EMR), almost 68% of all deaths are attributed to NCDs commonly known as chronic or lifestyle-related diseases. Two-thirds of NCD premature deaths are linked to 4 shared modifiable behavioral risk factors: tobacco use, u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
21
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(23 citation statements)
references
References 45 publications
0
21
2
Order By: Relevance
“…The national prevalence rate of raised total cholesterol was reported as 36% in the survey, which was in line with the global prevalence of raised total cholesterol (27). Our results are lower than a majority of Gulf countries where the prevalence was 50% or higher (28). The prevalence among women was higher than men, which also seemed to be the trend globally (27).…”
Section: Biological Risk Factorscontrasting
confidence: 62%
“…The national prevalence rate of raised total cholesterol was reported as 36% in the survey, which was in line with the global prevalence of raised total cholesterol (27). Our results are lower than a majority of Gulf countries where the prevalence was 50% or higher (28). The prevalence among women was higher than men, which also seemed to be the trend globally (27).…”
Section: Biological Risk Factorscontrasting
confidence: 62%
“…Thus, elimination of industrially produced TFA is achievable through two policy options recommended by WHO, that is, ban on partially hydrogenated fat or limit of TFA <2% of total fat in all fats and food products. During the past decade, several countries have virtually eliminated industrially produced TFA from the food supply through implementation of systematic policy actions and monitoring programs 9 . The REPLACE package issued by WHO in May 2018 serves as a roadmap for countries to implement actions to reduce and eliminate industrially produced TFA, and outlines six strategic action areas to support the prompt, complete, and sustained elimination of industrially produced TFA from the food supply 10 …”
Section: Introductionmentioning
confidence: 99%
“…Thus, it is also considered that its textural and olfactory characteristics are effective on preference (Besnard, 2016). However, excessive amounts and unhealthy types may play a role in the increased risk of developing chronic diseases including cardiovascular diseases and obesity, which is related to increased morbidity and mortality (Freeland‐Graves & Nitzke, 2013; Jawaldeh & Al‐Jawaldeh, 2018; Macronutrients, 2005). It has been shown that increased fat intake contributes to increased calorie intake resulting in increased body weight regardless of the types consumed (Vannice & Rasmussen, 2014).…”
Section: Introductionmentioning
confidence: 99%